2014
DOI: 10.1089/thy.2012.0567
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Degree of Extrathyroidal Extension of Disease on Papillary Thyroid Cancer Outcome

Abstract: Oncological outcome correlates with the extent of extrathyroidal invasion. Outcome is worse in patients with gross extrathyroidal disease extension than in those with microscopic local invasion apparent on histopathological assessment. However, the risk of clinical recurrence appears similar between patients undergoing margin-negative and "close margin" resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
98
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(105 citation statements)
references
References 11 publications
6
98
1
Order By: Relevance
“…Some studies have indicated that PTC patients with minimal or microscopic extension had worse prognostic outcomes than those with maximal or macroscopic extension [106][107][108]. However, ETE or microscopic local invasion is inconsistently defined and utilized among studies and there are a large number of studies which did not concern about various degrees of extrathyroidal extension.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated that PTC patients with minimal or microscopic extension had worse prognostic outcomes than those with maximal or macroscopic extension [106][107][108]. However, ETE or microscopic local invasion is inconsistently defined and utilized among studies and there are a large number of studies which did not concern about various degrees of extrathyroidal extension.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent studies attempts have been made to compare microscopic and macroscopic ETE, or absence of ETE and minimal and maximal ETE [2,15,18]. In other studies, ETE has been classified into four groups: with a negative margin versus a close margin, microscopic ETE, and gross ETE [14,15]. In yet another study, ETE was divided into the four groups, absence of ETE, minimal ETE, maximal ETE which could be shaved off, and maximal ETE that had invaded the recurrent laryngeal nerve, trachea and/or esophagus [21].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the outcome of macroscopic gross ETE was worse than that of microscopic local invasion [14][15][16][17]. However, in the previous studies the definition of ETE was neither clear nor constant.…”
Section: Introductionmentioning
confidence: 89%
“…The clinical importance of minimal extrathyroidal extension on outcome of PTC is not well established. However, several recent studies reported no significant difference in recurrence or recurrence-free survival between patients with and without minimal extrathyroidal invasion [11][12][13]. Nixon et al [12] reported no significant difference in 10-year OS, DSS or RFS between the pT1/pT2 and pT3 groups (OS: 93 vs. 88 %, p = 0.129; DSS: 99 vs. 100 %, p = 0.733; RFS: 98 vs. 95 %, p = 0.188, respectively).…”
Section: Ata Intermediate-risk Categorymentioning
confidence: 95%
“…In their meta-analysis, Sacks et al [8] concluded that 131 I remnant ablation did not improve survival or recurrence in patients aged <45 years with microscopic central compartment lymph node metastases, whereas benefit was uncertain in the setting of lateral or macroscopic lymph node metastases. More recently, some studies in which only intermediate-risk patients were evaluated, have been published [9][10][11][12][13][14]. Aggressive variant of PTC, such as diffuse sclerosing (DSV) and tall cell (TCV) variants, has a worse prognosis than classic PTC variant [9,10].…”
Section: Ata Intermediate-risk Categorymentioning
confidence: 99%